Teachers as Change Agents: Professional Development for Integrating SDGs into Pedagogy in Pakistani Context - Shariq, Muhammad; Imran, Quratulain; Maqbool, Saira (Journal of Development and Social Sciences, 2025)
The objective of the study is to investigating the professional learning and knowledge enhancement requirements of Pakistani educators in regard to implementation of SDG in context of their classrooms. The research is both quantitative and qualitative in nature which investigates how teachers, educational administrators and policymakers view the implementation of SDGs in their classrooms. The results show that despite the increasing concern about the SDGs, there are still problems that include a lack of preparation, insufficient funding and weak policy backing. According to these findings, the research provides a framework for the teacher professional development which comprises of trained programmes, curriculum change and the networking of learning. The study also calls for the facilitation of the necessary knowledge, skills and resources that teachers need for the integration of SDG into their teaching practices to support the realization of the quality education SDG 4 as well as the other related goals.